The Neural Correlates of Guilt and Restitution During a Social Decision Making Task - Ty, Ambrose (2014)
Guilt is a social emotion that promotes prosocial and moral behaviours. It arises as a result of harming another individual, serving as a prompt for the guilty individual to take reparative actions, known as restitution. The neural regions that are involved in guilt and restitution, however, are not currently known. To identify these regions, we employed a novel social decision-making fMRI paradigm involving donations to charities. There was a significant positive correlation between trait guilt and BOLD signal in the vlPFC and mPFC during acts of restitution. Furthermore, choices of harm when compared to help showed increased BOLD signal in the amygdala, insula, and the superior temporal sulcus. The present results are consistent with past studies that indicate an important role of the vlPFC and mPFC for processing aversive social cues and to resolve decision conflict